A Note on the Well-Posedness of Control Complex Ginzburg-Landau Equations in Zhidkov Spaces - Besteiro, A. (Trends in Computational and Applied Mathematics, 2022)
In this note, we consider the Complex Ginzburg-Landau equations with a bilinear control term in the real line. We prove well-posedness results concerned with the initial value problem for these equations in Zhidkov spaces using Splitting methods.